Turn your teams inside out : externally focused teams can drive innovation, performance, and distributed leadership, but adopting them requires a shift in mindset - Ancona, Deborah G. (Deborah Gladstein); Bresman, Henrik (MIT Sloan Management Review, 2022)
In a business environment characterized by accelerating change and growing uncertainty, teams whose orientation spans both the internal organization and the external business ecosystem are nimbler and drive more innovation — and also serve to distribute leadership throughout the organization. The authors review the challenges of successfully implementing the x-team model of collaboration and describe the success factors common among high-performing x-teams.